Elevated NLRP3 Inflammasome Levels Correlate With Vitamin D in the Vitreous of Proliferative Diabetic Retinopathy - Lu, Li; Zou, Gaocheng; Chen, Li; Lu, Qianyi; Wu, Mian; Li, Chunxia (Frontiers in Medicine, 2021)
Abstract： Purpose: This study aims to determine vitamin D concentrations in the vitreous and serum, as well as the expression levels of NLRP3 inflammasome pathway in the vitreous of patients with proliferative diabetic retinopathy (PDR). In addition, we investigated the possible correlation between NLRP3 inflammasome levels and vitamin D concentrations. Methods: We obtained vitreous samples before vitrectomy from 55 PDR patients, 25 non-diabetic patients with idiopathic macular hole (IMH), and 10 nonproliferative diabetic retinopathy (NPDR) patients. We also collected serum samples from the same patients. Enzyme-linked immunosorbent assay (ELISA) was used to examine NLRP3 Iinflammasome pathway proteins, including NLRP3, caspase-1, IL-1β, and VEGF. In addition, vitamin D concentrations were analyzed in Roche Cobas 6000’s module e601 platform by electrochemiluminescence immune assay. Results: The levels of NLRP3 inflammasome pathway and VEGF increased dramatically in PDR vitreous. However, vitamin D concentrations in vitreous and serum followed the opposite trend. Meanwhile, both vitreous and serum vitamin D concentrations significantly negatively correlated with vitreous NLRP3 expression in PDR patients. Moreover, serum and vitreous vitamin D concentrations were positively correlated and showed discriminatory ability in DR. The subgroup analysis of the PDR group revealed that eyes with tractional retinal detachment (TRD) had higher NLRP3 inflammasome pathway and VEGF levels but lower vitamin D concentrations. Conversely, eyes that received preoperative pan-retinal photocoagulation (PRP) exhibited lower levels of NLRP3 inflammasome pathway, but vitamin D concentrations were irrelevant to laser treatment. Conclusions: Our results demonstrate a strong correlation between increased NLRP3 inflammasome pathway and decreased vitamin D concentrations in the vitreous of PDR patients, which may be linked to PDR pathogenesis. In addition, vitamin D supplementation may play a key role in preventing, treating, and improving PDR prognosis due to its inhibitory impact on NLRP3 inflammasome pathway and VEGF